Lucy Sullivan is Getting Married - 181479 Keyes, Marian (New York : AVON BOOKS, 1996)
What happens when a psychic tells Lucy that she'll be getting married within the year? Her roommates panic! What is going to happen to their blissful existence of eating take-out, drinking too much wine, bringing men home, and never vacuuming?Lucy reassures her friends that she's far too busy arguing with her mother and taking care of her irresponsible father to get married. And then there's the small matter of not.